Analisis Pembelajaran Tematik melalui Penggunaan Sistem Pengelolaan Pembelajaran E-Learning dengan LMS Sederhana Berbasis WEBVIEW - Agustin, Ina; Widiyanti, Ifa Seftia Rakhma (JPB - Jurnal Pendidikan Biologi, 2022)
This study aims to describe the implementation of thematic learning, describe the learning outcomes of 5th grade elementary school students, the obstacles experienced, as well as efforts to overcome obstacles in the implementation of an e-learning learning management system with a simple webview-based LMS. This type of research is descriptive qualitative research. The subjects of this study were teachers and students of class V SDN Sumurjalak 1. The data collection techniques in this study were observation, interviews and documentation. Interviews were conducted directly with class teachers and students. Observations were made during thematic learning using an e-learning learning management system with a simple webview-based LMS. The data that has been collected is then reduced, then presented in the form of descriptions, tables and figures which are then given conclusions. The implementation of thematic learning in this study presents material on the theme of 6 sub-themes 1 class V, namely Heat and its Transfer. In this online learning, students use a simple LMS based on a webview. The LMS used is equipped with a platform that contains a summary of learning materials, learning videos and student worksheets that have been arranged coherently according to the learning steps with an interesting presentation. Student learning outcomes after using this LMS have increased. Students also feel happy and interested in participating in online learning with a simple LMS. However, in the implementation of thematic learning using LMS there are several obstacles including (1) Inadequate or limited quotas; (2) Unstable internet connection due to home environment conditions; (3) There is distraction in the home environment (noisy, often ordered to); (4) Insufficient device capacity to install online learning support applications and subject file storage. (5) late submission of assignments. Efforts made by schools and teachers in overcoming existing obstacles are trying their best to present interesting, creative and fun learning besides encouraging teachers to be creative and innovative in creating interesting online learning for students. availability of existing technological facilities, so that online learning can run as previously planned. Then to minimize delays in collecting assignments and following online learning the teacher can guide students to prepare in the previous days.